Donor Darah sebagai Wujud Kepedulian Sosial Mahasiswa Universitas Sunan Giri Surabaya Kepada Masyarakat - Rafida Febriana Widya Putri; Maria Widya Wanti; Khairunnisa Salsabila Putri Prameswari; Yeni Vitrianingsih; Novritsar Hasitongan Pakpahan; Rio Saputra; Dharma Setiawan Negara; Didit Darmawan; Rommy Hardyansah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The implementation of activities carried out by the Sunan Giri University Surabaya TIM in the form of blood donation activities on August 25 2024, is a form of social concern for the community. This activity uses the Asset Based Community Development (ABCD) method with observation, interviews and active participation from campus residents and the surrounding community. The main aim of this activity is to help patients who need blood transfusions and increase awareness of the importance of blood donation and social awareness. Held on the Sunan Giri University Surabaya campus, this activity is in collaboration with the Indonesian Red Cross (PMI) and involves hygienic and standard medical procedures. The results of the activity showed high enthusiasm from the participants, with more than 100 people registering as donors and around 50 bags of blood were collected. This activity not only fulfills the need for blood, but also strengthens relations between the university and the local community and encourages students to take an active role in social activities and play an active role in building wider social awareness.